Assessing Abstraction Skills. - Hazzan, Orit; Kramer, Jeff (Communications of the ACM, 2016)
The authors discuss abstraction as a significant skill in computer science (CS) and software engineering (SE) and whether abstraction skills are assessable. The authors argue that directly querying experts on whether abstraction are assessable would not produce a clear response, and propose a set of survey question patterns to assess abstraction skills.